Exploring quality improvement for diabetes care in First Nations communities in Canada: a multiple case study - Meghan Fournie; Shannon L. Sibbald; Stewart B. Harris (BMC, 2023)
Abstract Background Indigenous peoples in Canada experience higher rates of diabetes and worse outcomes than non-Indigenous populations in Canada. Strategies are needed to address underlying health inequities and improve access to quality diabetes care. As part of the national FORGE AHEAD Research Program, this study explores two primary healthcare teams' quality improvement (QI) process of developing and implementing strategies to improve the quality of diabetes care in First Nations communities in Canada. Methods This study utilized a community-based participatory and qualitative case study methodology. Multiple qualitative data sources were analyzed to understand: (1) how knowledge and information was used to inform the teams' QI process; (2) how the process was influenced by the context of primary care services within communities; and (3) the factors that supported or hindered their QI process. Results The findings of this study demonstrate how teams drew upon multiple sources of knowledge and information to inform their QI work, the importance of strengthening relationships and building relationships with the community, the influence of organizational support and capacity, and the key factors that facilitated QI efforts. Conclusions This study contributes to the ongoing calls for research in understanding the process and factors affecting the implementation of QI strategies, particularly within Indigenous communities. The knowledge generated may help inform community action and the future development, implementation and scale-up of QI programs in Indigenous communities in Canada and globally.